A binder and a preparation method thereof, a negative electrode and a lithium ion battery
Patent Information
- Application Number
- CN202510568948.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]专利CN112447973A公开了锂离子电池电极用粘合剂水溶液、锂离子电池电极用浆料、锂离子电池电极及锂离子电池的制备,该方法是通过将两种聚合物进行复配,虽然一定程度上提高了极片的抗膨胀性,但是极片偏脆,且制造工艺麻烦,因而提高了锂离子电池的加工成本
[0059]本发明通过采用无皂聚合,并且引入功能单体B中导离子结构基团如环氧乙烷与环氧丙烷,以及溶剂化链结构设计,再加上与羧基、羟基、氰基等官能团结合,使得粘结剂具有较好内聚力的同时,又具有很好的韧性、导离子性、抗膨胀性。
Smart Images

Figure BDA0005386611190000031 
Figure BDA0005386611190000111 
Figure BDA0005386611190000121
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy lithium-ion battery materials, and relates to a binder and its preparation method, a negative electrode and a lithium-ion battery. Specifically, it relates to a binder and its preparation method, a negative electrode containing the binder and a lithium-ion battery containing the negative electrode. Background Technology
[0002] With the global need for green energy development and the rapid growth in demand for new energy sources, lithium-ion batteries have been widely used in products such as mobile phones, computers, and electric vehicles, thus possessing immense commercial value. Silicon-based anodes, due to their advantages such as large capacity, can match the development of high-energy-density batteries. Therefore, developing high-capacity silicon-based materials (theoretical capacity 4200 mAh / g) has become a major challenge in lithium-ion battery technology development. However, because silicon-based materials experience greater volume expansion and contraction (up to 300%) during charging and discharging, the electrode capacity decays rapidly and cycle performance is poor. Therefore, it is necessary to develop binders with high bonding strength and the ability to uniformly disperse expansion stress to achieve the cycle stability of high-capacity anodes.
[0003] Although the binder used in lithium-ion batteries constitutes a small percentage, it plays a crucial role. The binder must effectively bond the active materials together and ensure adhesion between the active materials and conductive agents to the current collector. It plays a vital role in battery manufacturing and performance, making it an essential component of the battery. Currently, the most commonly used binders are polyvinylidene fluoride (PVDF) and styrene-butadiene copolymer (SBR). However, SBR contains emulsifiers, which can cause side effects, and SBR has poor conductivity, especially when used as a binder in silicon-based anodes, exhibiting poor resistance to expansion. Nowadays, silicon-based anode binders often use water-soluble polymers with high glass transition temperatures, such as polyacrylic acid polymers. While these water-soluble polymers can suppress the expansion of silicon-based anodes to some extent, their brittleness, lack of elasticity, poor processability, and susceptibility to cracking lead to poor battery cycle life. Although combining it with a typical SBR emulsion (particle size around 150-200nm) offers some improvement, it still doesn't fully solve the aforementioned problems of silicon-based anodes, and the combined use also complicates the battery processing. Therefore, there is an urgent need to develop a binder that can both suppress the expansion of silicon-based anodes and possess good processing and electrochemical properties.
[0004] Patent CN112447973A discloses an aqueous solution of adhesive for lithium-ion battery electrodes, a slurry for lithium-ion battery electrodes, a lithium-ion battery electrode, and a lithium-ion battery. This method involves compounding two polymers, which improves the resistance to expansion of the electrode to some extent. However, the electrode is brittle and the manufacturing process is complicated, thus increasing the processing cost of lithium-ion batteries.
[0005] Patent CN109860597A discloses an aqueous composite binder for lithium-ion batteries. The binder contains 5-50 wt% of ethylene vinyl acetate copolymer and 95-50 wt% of compound binder. The binder has the characteristics of high elongation at break and tensile strength, and good adhesion. It can simultaneously improve the specific capacity and cycle stability of lithium-ion batteries. However, the rate performance of lithium-ion batteries using this binder is still relatively poor.
[0006] Patent CN116830318A discloses a negative electrode adhesive composition, a negative electrode, and a secondary battery. The adhesive contains a copolymer with hydroxyl-containing monomer (a) and acid-containing monomer (b) as essential components. However, it requires a high molecular weight of the copolymer, and the cycle and rate performance of the battery using this adhesive are still insufficient. Summary of the Invention
[0007] To improve the above-mentioned technical problems, the present invention provides an adhesive comprising: a neutralizing agent, a hydrophilic monomer, a crosslinking monomer, a functional monomer A, a functional monomer B, a molecular weight regulator, an initiator, a reducing agent, a bactericide, and a dispersant.
[0008] According to an embodiment of the present invention, the raw materials for preparing the adhesive include a neutralizing agent, a hydrophilic monomer, a crosslinking monomer, a functional monomer A, a functional monomer B, a molecular weight regulator, an initiator, a reducing agent, a bactericide, and a dispersant.
[0009] According to an embodiment of the present invention, the neutralizing agent is at least one selected from ammonia, monoethanolamine, triethanolamine, 2-amino-2-methyl-1-propanol, sodium hydroxide, lithium hydroxide, potassium hydroxide, sodium carbonate, lithium carbonate, and potassium carbonate.
[0010] According to embodiments of the present invention, the hydrophilic monomer is acrylamide, acrylic acid, sodium acrylate, lithium acrylate, potassium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, potassium methacrylate, sodium allyloxyhydroxypropyl sulfonate, potassium allyloxyhydroxypropyl sulfonate, lithium allyloxyhydroxypropyl sulfonate, potassium allyloxyhydroxypropyl sulfonate, vinyl sulfonic acid, lithium vinyl sulfonate, sodium vinyl sulfonate, potassium vinyl sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, sodium 2-acrylamide-2-methylpropanesulfonate, lithium 2-acrylamide-2-methylpropanesulfonate, 2-acrylamide-2-methylpropanesulfonate, amine 2-acrylamide-2- Potassium methylpropanesulfonate, sodium propylene sulfonate, potassium propylene sulfonate, ammonium propylene sulfonate, methylpropylene sulfonic acid, sodium methylpropylene sulfonate, ammonium methylpropylene sulfonate, lithium methylpropylene sulfonate, potassium methylpropylene sulfonate, itaconic acid, ammonium itaconicate, sodium itaconicate, lithium itaconicate, potassium itaconicate, ammonium itaconicate, sodium maleate, ammonium maleate, sodium maleate, lithium maleate, potassium maleate, methacrylamide, N-ethylacrylamide, N-butylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, sodium 2-acrylamido-2-methylpropanesulfonic acid, lithium 2-acrylamido-2-methylpropanesulfonic acid, and 2-acrylamido-2-phenylethanesulfonic acid.
[0011] According to an embodiment of the present invention, the crosslinking monomer is a monomer having two or more unsaturated double bonds. For example, it is selected from at least one of polyethylene glycol dimethacrylate, trimethylolpropene triacrylate, N-methylenebisacrylamide, divinyl phthalate, and 1,6-hexanediol dimethacrylate.
[0012] According to an embodiment of the present invention, the functional monomer A is at least one selected from acrylonitrile, methacrylonitrile, 2-methacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, allyl urea, methacrylamide ethyl ethylene urea, urea methacrylate, docosyl alcohol polyoxyethylene ether methacrylate, triphenylethylphenol polyoxyethylene ether methacrylate, methacrylate polyoxyethylene ether, allyloxyhydroxypropyl sulfonic acid and its potassium, sodium, and lithium salts, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, and 4-hydroxybutyl methacrylate.
[0013] According to an embodiment of the present invention, the functional monomer B is a water-soluble alkenyl block polyether having the following structure:
[0014]
[0015] Wherein, R is selected from at least one of 2-methylallyloxy, methylallyloxy, isopentenoxy and 4-butylethoxy; x and y are the same or different, and are independent integers from 5 to 100, preferably integers from 10 to 70, and x+y>10.
[0016] In this invention, "water solubility" means that when 0.1g of the compound is dissolved in 100g of water at 23°C, the insoluble component is less than 2mg.
[0017] According to an embodiment of the present invention, the molecular weight regulator is at least one of dodecyl mercaptan, methylstyrene dimer, tert-dodecyl mercaptan, and mercaptopropionic acid.
[0018] According to an embodiment of the present invention, the initiator is at least one selected from benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, sodium hypochlorite, hydrogen peroxide, and azobisisobutyranidine.
[0019] According to an embodiment of the present invention, the reducing agent is at least one selected from sodium sulfite, sodium bisulfite, sodium formaldehyde sulfoxylate, and L-ascorbic acid.
[0020] According to an embodiment of the present invention, the bactericide is at least one of BIT (benzisothiazolinone), CIT (isothiazolinone), and Kathon.
[0021] According to an embodiment of the present invention, the dispersant is water.
[0022] According to an embodiment of the present invention, the adhesive, by weight, comprises the following components in the following proportions:
[0023] The neutralizing agent accounts for 1-20% of the total mass of the monomers;
[0024] The initiator accounts for 0.01-3% of the total mass of the monomer;
[0025] The reducing agent accounts for 0.01-3% of the total mass of the monomer;
[0026] The hydrophilic monomer accounts for 10-90% of the total mass of the monomer;
[0027] The functional monomer A accounts for 5-50% of the total mass of the monomer;
[0028] The functional monomer B accounts for 3-40% of the total mass of the monomer;
[0029] The crosslinking monomer accounts for 0.003-5% of the total monomer mass;
[0030] The molecular weight regulator accounts for 0.003-5% of the total mass of the monomer;
[0031] The bactericide accounts for 0.003-2% of the total mass of the monomer.
[0032] According to an embodiment of the present invention, the effective solid content of the adhesive is 6-20%, preferably 10-20%.
[0033] According to an embodiment of the present invention, the viscosity of the adhesive is 1000-30000 cps, preferably 3000-20000 cps.
[0034] According to an embodiment of the present invention, the pH of the adhesive is 5-9, preferably 6.5-8.5.
[0035] The present invention also provides a method for preparing the above-mentioned adhesive, the method comprising mixing a neutralizing agent, a hydrophilic monomer, a crosslinking monomer, a functional monomer A, a functional monomer B, a molecular weight regulator, an initiator, a reducing agent, a bactericide, and a dispersant to prepare the adhesive.
[0036] According to an embodiment of the present invention, the method for preparing the adhesive comprises the following steps:
[0037] (1) Mix the dispersant with the hydrophilic monomer, crosslinking monomer, functional monomer A, functional monomer B, and molecular weight regulator to prepare a mixed solution;
[0038] (2) Increase the temperature and simultaneously add the initiator aqueous solution and the reducing agent aqueous solution to the mixed solution in step (1) to carry out the polymerization reaction;
[0039] (3) After the polymerization reaction is completed, cool to room temperature and add a neutralizing agent to adjust the pH to 5-9;
[0040] (4) Add bactericide and dispersant to adjust the effective solid content, viscosity and pH of the adhesive to obtain the adhesive.
[0041] In some embodiments, the preparation method further includes filtering the obtained adhesive to obtain the final product.
[0042] In some embodiments, the mixing in step (1) is carried out under an inert atmosphere. For example, the inert atmosphere may be nitrogen or argon.
[0043] In some embodiments, in step (1), the mixing temperature is 5 to 30°C, for example, room temperature.
[0044] In some embodiments, in step (2), the initiator aqueous solution and the reducing agent aqueous solution are added to the mixed solution dropwise. For example, the dropwise addition time is 1-10 hours, exemplarily 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0045] In some embodiments, in step (2), the concentration of the initiator aqueous solution is 0.1-5%, exemplarily 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4% or 5%.
[0046] In some embodiments, in step (2), the concentration of the reducing agent aqueous solution is 0.1-5%, exemplarily 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4% or 5%.
[0047] In some implementations, in step (2), the temperature is raised to 35-80°C, for example 35°C, 40°C, 50°C, 60°C, 70°C or 80°C.
[0048] In some embodiments, in step (2), the temperature of the polymerization reaction is 35-80°C, for example 35°C, 40°C, 50°C, 60°C, 70°C or 80°C; the time of the polymerization reaction is 1-16h, for example 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h.
[0049] The present invention also provides the application of the binder in the preparation of lithium-ion battery anode sheets.
[0050] The present invention also provides a negative electrode sheet comprising the above-described binder.
[0051] According to an embodiment of the present invention, the amount of binder in the negative electrode sheet is 1.5% to 3%, exemplarily 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3%.
[0052] According to an embodiment of the present invention, the negative electrode sheet further includes a negative electrode active material and a conductive agent.
[0053] According to an embodiment of the present invention, the negative electrode active material may be natural graphite, artificial graphite, or silicon-carbon negative electrode material.
[0054] According to an embodiment of the present invention, the conductive agent may be at least one of conductive carbon black and conductive graphite.
[0055] According to an embodiment of the present invention, in the negative electrode sheet, the mass ratio of the negative electrode active material, binder and conductive agent is (90-98):(1.5-3):(0.5-7), preferably 96.5:2.5:1.
[0056] The present invention also provides a lithium-ion battery comprising the above-described negative electrode.
[0057] According to an embodiment of the present invention, the lithium-ion battery further includes a positive electrode, an electrolyte, and a separator.
[0058] The beneficial effects of this invention are:
[0059] This invention employs soap-free polymerization and introduces ion-conducting structural groups such as ethylene oxide and propylene oxide into functional monomer B, along with solvation chain structure design and combination with functional groups such as carboxyl, hydroxyl, and cyano groups. This results in an adhesive that possesses good cohesion, as well as excellent toughness, ion conductivity, and anti-swelling properties.
[0060] The binder of this invention has low preparation cost, uses water as a solvent, and is safe, environmentally friendly, non-toxic, and easy to process. Compared with the existing negative electrode binder dosage of 3-5.5%, the binder dosage of this invention is only 2.0-3%.
[0061] The binder of the present invention has high adhesion and anti-expansion properties when applied to graphite and silicon-based anodes, especially high-capacity silicon-based anodes. This results in strong adhesion between the battery electrode and copper foil, and good flexibility of the electrode. Consequently, the battery using this anode has high initial coulombic efficiency, excellent rate performance, and low impedance, while also improving the battery's cycle life and other performance characteristics. Detailed Implementation
[0062] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Of course, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0063] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0064] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0065] Example 1
[0066] The preparation method of the adhesive is as follows:
[0067] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g acrylic acid, 1g polyethylene glycol dimethacrylate, 20g acrylonitrile, 30g acrylamide, and 20g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 10 -[CH2CH2O]15 Add 0.5g dodecyl mercaptan (-H), turn on the stirrer, and heat in a water bath to 50°C;
[0068] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1; weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2;
[0069] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0070] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration of 10%) to adjust the pH to 7;
[0071] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and after passing the test, filter and package the product using a 300-micron filter screen to obtain the final product.
[0072] Example 2
[0073] The preparation method of the adhesive is as follows:
[0074] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 20g acrylic acid, 0.5g polyethylene glycol dimethacrylate, 10g acrylonitrile, 30g acrylamide, and 40g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 10 -[CH2CH2O] 20 Add 0.5g of dodecyl mercaptan (-H), turn on the stirrer and simultaneously introduce nitrogen gas, then turn on the water bath to heat to 50°C.
[0075] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain a mixed solution 1; weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form a mixed solution 2.
[0076] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0077] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0078] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0079] Example 3
[0080] The preparation method of the adhesive is as follows:
[0081] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 15g methacrylic acid, 0.5g polyethylene glycol dimethacrylate, 10g acrylonitrile, 35g acrylamide, and 40g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 20 -[CH2CH2O] 40 Add 0.5g of dodecyl mercaptan (-H), turn on the stirrer and simultaneously introduce nitrogen gas, then turn on the water bath to heat to 50°C;
[0082] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0083] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0084] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0085] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0086] Example 4
[0087] The preparation method of the adhesive is as follows:
[0088] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g methacrylic acid, 1g polyethylene glycol dimethacrylate, 15g acrylonitrile, 15g acrylamide, and 40g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 20 -[CH2CH2O] 70 Add 0.5g of dodecyl mercaptan (-H), turn on the stirrer and simultaneously introduce nitrogen gas, then turn on the water bath to heat to 50°C;
[0089] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0090] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0091] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0092] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0093] Example 5
[0094] The preparation method of the adhesive is as follows:
[0095] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 35g methacrylic acid, 1g polyethylene glycol dimethacrylate, 10g acrylonitrile, 15g acrylamide, and 40g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 20 -[CH2CH2O] 65 Add 0.5g of dodecyl mercaptan (-H), turn on the stirrer and simultaneously introduce nitrogen gas, then turn on the water bath to heat to 50°C;
[0096] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0097] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0098] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0099] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0100] Comparative Example 1
[0101] The preparation method of the adhesive is as follows:
[0102] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g acrylic acid, 1g polyethylene glycol dimethacrylate, 20g acrylonitrile, 30g acrylamide, and 20g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH2O)) to the reactor. 20 Add 0.5g dodecyl mercaptan (-H), turn on the stirrer, and heat in a water bath to 50°C;
[0103] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0104] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0105] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0106] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0107] Comparative Example 2
[0108] The preparation method of the adhesive is as follows:
[0109] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g acrylic acid, 1g polyethylene glycol dimethacrylate, 20g acrylonitrile, 30g acrylamide, and 20g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 15 Add 0.5g dodecyl mercaptan (-H), turn on the stirrer, and heat in a water bath to 50°C;
[0110] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1. Weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0111] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0112] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0113] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0114] Comparative Example 3
[0115] The preparation method of the adhesive is as follows:
[0116] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g acrylic acid, 1g polyethylene glycol dimethacrylate, 20g acrylonitrile, 50g acrylamide and 0.5g dodecyl mercaptan to the reactor, turn on the stirrer and simultaneously introduce nitrogen gas, and turn on the water bath to heat to 50°C.
[0117] (2) Weigh out 1g of prepared ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1. Weigh out 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0118] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0119] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0120] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0121] Comparative Example 4
[0122] The preparation method of the adhesive is as follows:
[0123] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 10g methacrylic acid, 1g polyethylene glycol dimethacrylate, 10g acrylonitrile, 10g acrylamide, and 70g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O)) to the reactor. 20 -[CH2CH2O] 65 Add 0.5g of dodecyl mercaptan (-H), turn on the stirrer and simultaneously introduce nitrogen gas, then turn on the water bath to heat to 50°C;
[0124] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0125] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0126] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0127] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0128] Comparative Example 5
[0129] The preparation method of the adhesive is as follows:
[0130] (1) Under room temperature and nitrogen atmosphere, add 500g deionized water, 30g acrylic acid, 1g polyethylene glycol dimethacrylate, 20g acrylonitrile, 30g acrylamide, 20g methyl allyl alcohol block polyether (CH2=C(CH3)CH2-O-[CH2CH(CH3)O]5-[CH2CH2O]2-H), and 0.5g dodecyl mercaptan to the reactor, turn on the stirrer, and turn on the water bath to heat to 50℃;
[0131] (2) Weigh 1g of ammonium persulfate and dissolve it in 50g of deionized water to obtain mixed solution 1, and weigh 1g of sodium formaldehyde sulfoxylate and dissolve it in 50g of deionized water to form mixed solution 2.
[0132] (3) After the temperature rises to 50℃, add mixed solution 1 and mixed solution 2 dropwise at the same time. After adding for 8 hours, continue to keep the temperature for another 8 hours.
[0133] (4) After the reaction is complete, cool to room temperature and add 166g of sodium hydroxide aqueous solution (concentration 10%) to adjust the pH to 7;
[0134] (5) Finally, add 0.2g of bactericide BIT, add the remaining deionized water to adjust the basic physical properties such as (solid content %), viscosity, pH, and filter and package the product after it is qualified to obtain the final product.
[0135] Comparative Example 6
[0136] A mixed binder using Daicel's sodium carboxymethyl cellulose (CMC) for batteries and JSR's TRD104A styrene-butadiene rubber latex (SBR) is used, with a mass ratio of CMC to SBR of 1:1 in the mixed binder.
[0137] Comparative Example 7
[0138] Commercially available battery-grade polyacrylic acid (PAA) adhesive is used.
[0139] Performance testing
[0140] Electrolyte swelling degree test:
[0141] 5g of the effective solid content of the adhesive from each embodiment and comparative example was poured into a tetrafluoroethylene mold. After standing at room temperature for 24 hours, the mold was dried in an 80℃ oven to form a film. The dried film was cut into 18mm diameter discs. The above sample was weighed and recorded as m0. The film sample was placed in a mixed solvent containing ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DMC) in a mass ratio of 1:1:1, along with 5% FEC and 1M LiPF6 as electrolyte. Every 24 hours, the sample was removed, the surface electrolyte was wiped dry, and the weight was recorded as m1. Monitoring was conducted for at least 7 days, and the liquid absorption rate was calculated using the following formula: Liquid absorption rate = (m1 - m0) / m0 × 100%.
[0142] Slurry coating performance test:
[0143] A negative electrode slurry was prepared by mixing and dispersing the following components in a homogenizer for 3 hours: 96.5 wt% silicon-carbon anode (capacity 600 mAh / g), 1.0 wt% conductive carbon black (super-p), and 2.5 wt% binder (based on solid content). The balance was deionized water. The slurry had an effective solid content of 50%.
[0144] The viscosity of the above negative electrode slurry was tested using a Brookfield viscosity tester. The slurry viscosity was required to be 2000-6000 cps for coating. The slurry was coated on the current collector copper foil, and the coating performance was evaluated by observing whether there were pits, particles, uniformity, or exposed foil.
[0145]
[0146] Peel strength test:
[0147] The above negative electrode slurry was filtered through a 100-300 mesh sieve, coated onto an 8μm thick copper foil used as a current collector, dried at 80°C for 4 hours, and then naturally cooled to room temperature in the furnace.
[0148] The prepared electrode sheet was cut into strips of 20cm × 2.5cm. A 1mm thick steel plate was glued to the current collector side with double-sided adhesive tape, and transparent tape was pasted on the coating layer side. The electrode sheet was peeled off in a 180° direction at a speed of 100mm / min using a tensile testing machine, and the peeling stress was measured.
[0149] Electrode flexibility test:
[0150] After the prepared electrode sheet is rolled and wound onto a mandrel with a diameter of Φ1.5mm, it is laid flat and its condition is observed through an optical microscope. An intact electrode sheet is recorded as grade 5, and an electrode sheet that has fallen off or cracked is recorded as grade 0.
[0151] Initial charge / discharge capacity, cycle life, and electrode expansion rate tests:
[0152] Using silicon-carbon negative electrode sheets made with binders from the various embodiments and comparative examples as test electrodes, lithium metal as counter electrodes, and a mixture of ethylene carbonate EC, methyl ethyl carbonate EMC, and diethyl carbonate DMC in a mass ratio of 1:1:1 as a solvent, along with 5% FEC and 1M LiPF6 as electrolyte, and PE material as a separator, a CR2032 lithium-ion button battery was fabricated.
[0153] The above-mentioned lithium-ion coin cells were aged at 25°C, within a voltage range of 0.01-1.5V, at 0.1C. The first coulombic efficiency of the charge-discharge cycle and the capacity retention rate after 50 cycles at 0.5C were tested using the constant current method. After 50 charge-discharge cycles, the ratio of the increase in electrode thickness to the electrode thickness before charge-discharge was recorded as the electrode expansion rate, with the electrode in the lithium-intercalated state. The results are shown in Table 1 below.
[0154] Table 1. Performance test results of the binder and the CR2032 lithium-ion button batteries used in each embodiment and comparative example.
[0155]
[0156] The above results indicate that, compared to the SBR binder system, the binder of the present invention has a lower electrolyte swelling degree, can maintain flexibility at room temperature, and maintains the adhesion between active materials and between active materials and current collectors during the electrode fabrication process and cycling process, and has better rate capability and cycling performance.
[0157] In summary, the aqueous negative electrode binder of this invention significantly outperforms competing products in terms of rate capability, cycle life, initial charge / discharge capacity, anti-swelling properties, and processing performance. This invention, through soap-free polymerization and the introduction of ion-conducting structural groups and solvated chain structure design, enables the binder to possess both good cohesive strength and excellent toughness, ion conductivity, and anti-swelling properties. When applied to graphite and silicon-based negative electrodes, especially high-capacity silicon-based negative electrodes, the binder exhibits excellent anti-swelling properties, resulting in strong adhesion between the battery electrode and copper foil, good electrode flexibility, and consequently, high initial coulombic efficiency, excellent rate performance, and improved cycle life of lithium-ion batteries using this negative electrode.
[0158] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An adhesive, characterized in that, The binder comprises: a neutralizing agent, a hydrophilic monomer, a crosslinking monomer, a functional monomer A, a functional monomer B, a molecular weight regulator, an initiator, a reducing agent, a bactericide, and a dispersant.
2. The adhesive as claimed in claim 1, characterized in that, The neutralizing agent is at least one selected from ammonia, monoethanolamine, triethanolamine, 2-amino-2-methyl-1-propanol, sodium hydroxide, lithium hydroxide, potassium hydroxide, sodium carbonate, lithium carbonate, and potassium carbonate. And / or, the hydrophilic monomer is acrylamide, acrylic acid, sodium acrylate, lithium acrylate, potassium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, potassium methacrylate, sodium allyloxypropyl sulfonate, potassium allyloxypropyl sulfonate, lithium allyloxypropyl sulfonate, potassium allyloxypropyl sulfonate, vinyl sulfonic acid, lithium vinyl sulfonate, sodium vinyl sulfonate, potassium vinyl sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, sodium 2-acrylamide-2-methylpropanesulfonate, lithium 2-acrylamide-2-methylpropanesulfonate, 2-acrylamide-2-methylpropanesulfonic acid ... Potassium sulfonate, sodium propylene sulfonate, potassium propylene sulfonate, ammonium propylene sulfonate, methpropylene sulfonic acid, sodium propylene sulfonate, ammonium propylene sulfonate, lithium propylene sulfonate, potassium propylene sulfonate, itaconic acid, ammonium itaconicate, sodium itaconicate, lithium itaconicate, potassium itaconicate, ammonium itaconicate, sodium maleate, ammonium maleate, sodium maleate, lithium maleate, potassium maleate, methacrylamide, N-ethylacrylamide, N-butylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, sodium 2-acrylamido-2-methylpropanesulfonic acid, lithium 2-acrylamido-2-methylpropanesulfonic acid, and at least one of 2-acrylamido-2-phenylethanesulfonic acid; And / or, the crosslinking monomer is a monomer having two or more unsaturated double bonds. For example, it is selected from at least one of polyethylene glycol dimethacrylate, trimethylolpropene triacrylate, N-methylenebisacrylamide, divinyl phthalate, and 1,6-hexanediol dimethacrylate; And / or, the functional monomer A is acrylonitrile, methacrylonitrile, 2-methacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, hydroxyethyl acrylate, or hydroxyacrylate. Propyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, allyl urea, methacrylamide ethyl ethylene urea, urea methacrylate, docosyl alcohol polyoxyethylene ether methacrylate, triphenylethylphenol polyoxyethylene ether methacrylate, methacrylate polyoxyethylene ether, allyloxyhydroxypropyl sulfonic acid and its potassium, sodium and lithium salts, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate and 4-hydroxybutyl methacrylate; And / or, the functional monomer B is a water-soluble alkenyl block polyether having the following structure: Wherein, R is selected from at least one of 2-methylallyloxy, methylallyloxy, isopentenoxy and 4-butylethoxy; x and y are the same or different, are independent integers from 5 to 100, preferably integers from 10 to 70, and x+y>10. And / or, the molecular weight regulator is at least one of dodecyl mercaptan, methylstyrene dimer, tert-dodecyl mercaptan and mercaptopropionic acid; And / or, the initiator is at least one of benzoyl peroxide, dicumyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, sodium hypochlorite, hydrogen peroxide, and azobisisobutyramidine; And / or, the reducing agent is at least one of sodium sulfite, sodium bisulfite, sodium formaldehyde sulfoxylate, and L-ascorbic acid; And / or, the bactericide is at least one of BIT (benzisothiazolinone), CIT (isothiazolinone), and Kathon; And / or, the dispersant is water.
3. The adhesive as described in claim 1 or 2, characterized in that, The adhesive, by weight, comprises the following components in the following proportions: The neutralizing agent accounts for 1-20% of the total mass of the monomers; The initiator accounts for 0.01-3% of the total mass of the monomer; The reducing agent accounts for 0.01-3% of the total mass of the monomer; The hydrophilic monomer accounts for 10-90% of the total mass of the monomer; The functional monomer A accounts for 5-50% of the total mass of the monomer; The functional monomer B accounts for 3-40% of the total mass of the monomer; The crosslinking monomer accounts for 0.003-5% of the total monomer mass; The molecular weight regulator accounts for 0.003-5% of the total mass of the monomer; The bactericide accounts for 0.003-2% of the total mass of the monomer.
4. The adhesive according to any one of claims 1-3, characterized in that, The effective solids content of the adhesive is 6-20%, preferably 10-20%; And / or, the viscosity of the adhesive is 1000-30000 cps, preferably 3000-20000 cps; And / or, the pH of the adhesive is 5-9, preferably 6.5-8.
5.
5. A method for preparing the adhesive according to any one of claims 1-4, characterized in that, The preparation method includes mixing a neutralizing agent, a hydrophilic monomer, a crosslinking monomer, a functional monomer A, a functional monomer B, a molecular weight regulator, an initiator, a reducing agent, a bactericide, and a dispersant to prepare the adhesive.
6. The preparation method according to claim 5, characterized in that, The steps are as follows: (1) Mix the dispersant with the hydrophilic monomer, crosslinking monomer, functional monomer A, functional monomer B, and molecular weight regulator to prepare a mixed solution; (2) Increase the temperature and simultaneously add the initiator aqueous solution and the reducing agent aqueous solution to the mixed solution in step (1) to carry out the polymerization reaction; (3) After the polymerization reaction is completed, cool to room temperature and add a neutralizing agent to adjust the pH to 5-9; (4) Add bactericide and dispersant to adjust the effective solid content, viscosity and pH of the adhesive to obtain the adhesive.
7. The application of the adhesive according to any one of claims 1-4 and / or the adhesive prepared by the preparation method according to any one of claims 5-6 in the preparation of lithium-ion battery negative electrode sheets.
8. A negative electrode sheet, characterized in that, It includes the adhesive as described in any one of claims 1-4 and / or the adhesive prepared by the preparation method described in any one of claims 5-6.
9. The negative electrode sheet as described in claim 8, characterized in that, In the negative electrode sheet, the amount of binder is 1.5-3%; And / or, in the negative electrode sheet, the mass ratio of the negative electrode active material, binder and conductive agent is (90-98):(1.5-3):(0.5-7).
10. A lithium-ion battery, characterized in that, It includes the negative electrode sheet as described in claim 8 or 9.
Citation Information
Patent Citations
Waterborne compound adhesive for lithium ion battery
CN109860597A
